Modification of dijkstra's algorithm for safest and shortest path during emergency evacuation - Khyrina Airin Fariza, Abu Samah; Burairah, Hussin; Abd Samad, Hasan Basari (Hikari Ltd., 2015)
Intelligent autonomous evacuation navigation (AEN) system manages to solve wayfinding problems during emergency evacuation, especially for those who are not familiar with the building. AEN system is expected to provide independent evacuation navigation through the dynamic signage, which helps occupants navigate to the safest and shortest path towards the nearest exit. It uses modified Dijkstra's algorithm in order to incorporate both aspects and considering the hazardous location. Therefore, this paper presents the methodology used for the modification of Dijkstra's algorithm to find the safest and shortest path. The first modification involved the restriction of floor plan node's direction; and the second modification was blocking the nodes that affected by fire. The example is presented to compare the result obtained using the modified algorithm. Thus, it reveals the effectiveness of the modification in determining the best path for the evacuation process.